2018
DOI: 10.1007/s11356-018-2388-1
|View full text |Cite
|
Sign up to set email alerts
|

How does intensification influence the operational and environmental performance of photo-Fenton processes at acidic and circumneutral pH

Abstract: This study evaluates the technical, economical, and environmental impact of sodium persulfate (NaSO) as an enhancing agent in a photo-Fenton process within a solar-pond type reactor (SPR). Photo-Fenton (PF) and photo-Fenton intensified with the addition of persulfate (PFPS) processes decolorize 97% the azo dye direct blue 71 (DB71) and allow producing a highly biodegradable effluent. Intensification with persulfate allowed reducing treatment time in 33% (from 120 to 80 min) and the consumption of chemical auxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Many studies have been devoted to applying modifications in order to circumvent the drawbacks associated with conventional Fenton and Fenton-like processes. Among many others, use of different sources of oxyradicals, photo irradiation, ultrasound, and electrochemical methods have been tested for their intensified performance [16][17][18][19]. In this sense, addition of chelating agents in the reaction system could prevent precipitation of iron in the solution at higher pH (6.0-7.0) by forming stable chelates with iron ions and promoting its availability for hydroxyl radical generation from peroxide in a wider pH range [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been devoted to applying modifications in order to circumvent the drawbacks associated with conventional Fenton and Fenton-like processes. Among many others, use of different sources of oxyradicals, photo irradiation, ultrasound, and electrochemical methods have been tested for their intensified performance [16][17][18][19]. In this sense, addition of chelating agents in the reaction system could prevent precipitation of iron in the solution at higher pH (6.0-7.0) by forming stable chelates with iron ions and promoting its availability for hydroxyl radical generation from peroxide in a wider pH range [13].…”
Section: Introductionmentioning
confidence: 99%
“…During our research on the catalytic decomposition of H 2 O 2 using Pd or Pt-coated tubular reactors, we found that the catalytic conversion of H 2 O 2 to hydroxyl radicals increased with increasing pH using oxidized Pd-coated tubular reactors at room temperature [191,222]. The optimized range of pH was described as 6–9.…”
Section: Factors Affecting Catalytic Activitymentioning
confidence: 99%
“…It is reported in many research papers that an increase in operational temperature could be beneficial for both the oxidation rate and the extent of the catalytic decomposition of synthetic dyes [218,222], whereas very limited research has been conducted to evaluate the influence of experimental temperature conditions on the performance of the catalyst for the decomposition of synthetic dyes. Mostly, Fenton-based methods have been carried out at room temperature [223].…”
Section: Factors Affecting Catalytic Activitymentioning
confidence: 99%